CERAI TALAK YANG TERINDIKASI KDRT PERSPEKTIF UU NOMOR 23 TAHUN 2004 TENTANG KDRT DAN HUKUM ISLAM (Studi Putusan Nomor 70/Pdt.G/2020/PA.Pyk) - Adriantito Ramadhan; Irma Suryani (Institut Agama Islam Negeri Batusangkar, 2021)
This study aims to explain how the judge's legal considerations in decision number 70/Pdt.G/2020/PA.Pyk who provide a living for the wife indicated by nusyuz and to explain how the judge's legal considerations in the decision are reviewed from the PKDRT Law and Islamic Law. This research is a field research. The primary data source is information from the chairman of the panel of judges who decided the case, and the decision. Secondary data sources are obtained from library materials by searching for data or information in the form of written objects such as books, regulatory documents related to research. This study found, firstly, the nusyuz status of the wife according to the judge's opinion had no cause. The act of nusyuz in question is that the wife leaves the joint residence without the husband's permission in the condition that the household is still fine, and the husband does not state and prove that his wife is nusyuz. Then the wife in this case sued the husband back so that he was given a living while the husband agreed with his ability so that the judge stated there was no reason not to give the husband a living obligation to his wife. However, if viewed from the perspective of material law, namely KHI, the respondent is categorized as a wife who is nusyuz and her husband's livelihood is hindered either when she is nusyuz or divorced due to the nusyuz. Second, regarding the point of view of the PKDRT Law regarding indications of neglect from the wife based on her obligations according to Article 34 paragraph (2) of the Marriage Law, she cannot carry out her obligations under the law so that she is categorized as neglect based on Article 9 paragraph (1) of the PKDRT Law. Meanwhile, based on the judge's statement, the husband is the perpetrator of neglect after being analyzed based on his obligations in Article 34 paragraph (1) cannot completely violate the article, because the husband based on his ability is still carrying out his obligations to provide a living for his wife and children. Third, from the point of view of Islamic law regarding nusyuz. The scholars agree that the attitude of a wife who leaves the joint residence without the husband's permission is included in the act of nusyuz and the act of nusyuz resulting in the obstruction of a living from the husband to his wife.